Revisiting the nomenclature and taxonomy of the Malagasy Kalanchoe fedtschenkoi, and description of K. fedtschenkoi var. boiteaui (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F. (Phytotaxa, 2024)
The taxonomy and nomenclature of Kalanchoe fedtschenkoi (Crassulaceae subfam. Kalanchooideae) are revisited. Kalanchoe fedtschenkoi var. boiteaui is described here for material previously referred to under the designation “Kalanchoe fedtschenkoi var. isalensis”. Cultivar names and what are likely trade designations linked to the species name K. fedtschenkoi are catalogued.